Pemikiran dan Implikasi Pendidikan Islam KH. Ahmad Dahlan Terhadap Pendidikan Islam Kontemporer - Rahma Tiara Azzahra; M Yunus Abu Bakar (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2023)
The background of this research stems from the researcher's curiosity towards Muhammadiyah schools, which number in the hundreds or even thousands that were established because of the ideas of KH. Ahmad Dahlan. More precisely not the school, but the extraordinary thinking about Islamic Religious Education. Islamic education has a big role in determining the fate of the nation. The distribution of education is considered uneven, especially in remote areas. For this reason, KH. Ahmad Dahlan (Founder of Muhammadiyah) contributed to the results of the embodiment of his thoughts in seeing the problems that arise in indigenous territories. The purpose of this research is to find out what is the background of KH. Ahmad Dahlan and his thoughts on Islamic Education and their implications for contemporary Islamic education. From the research that has been done, the researchers obtained the results of KH. Ahmad Dahlan's background is: concern for indigenous Muslims, educational gaps, resistance to Christianity. While the thoughts of KH. Ahmad Dahlan in the world of Islamic Education is: 1) Establishing schools, 2) Born Ulama' reasons, 3) Collaborating with the Dutch government, 4) Adopting the education system, 5) Da'wah. Then for the implications in KH's thinking. Ahmad Dahlan's contemporary Islamic education includes 3 aspects, namely: learning materials, learning methods and educational goals.